2001
DOI: 10.1021/jo015788y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 1α-Fluoro A-Ring Phosphine Oxide, a Useful Building Block for Vitamin D Analogues, from (S)-Carvone via a Highly Selective Palladium-Catalyzed Isomerization of Dieneoxide to Dieneol

Abstract: The 1alpha-fluoro A-ring phosphine oxide 1, a useful building block for fluorinated vitamin D analogues, was synthesized from (S)-carvone in 13 synthetic steps, and only five isolations, in 22% overall yield. In the key synthetic step, a highly selective palladium-catalyzed isomerization of dieneoxide 18 to dieneol 20 was achieved using an appropriately selected fluorinated alcohol as a catalytic proton source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 23 publications
4
26
1
Order By: Relevance
“…The influence of the experimental conditions on the selectivity was also reported by Radinov and co‐workers, who studied the isomerization of the diene epoxide shown in Equation (68) 100. Whereas with PPh 3 , P(2‐furyl) 3 , or dppe as the ligands, mixtures of a dienol and an α,β‐unsaturated ketone were obtained, it was serendipitously observed that the addition of a fluorinated alcohol increased the formation of the alcohol with respect to the ketone.…”
Section: Alkenyl Epoxidessupporting
confidence: 60%
“…The influence of the experimental conditions on the selectivity was also reported by Radinov and co‐workers, who studied the isomerization of the diene epoxide shown in Equation (68) 100. Whereas with PPh 3 , P(2‐furyl) 3 , or dppe as the ligands, mixtures of a dienol and an α,β‐unsaturated ketone were obtained, it was serendipitously observed that the addition of a fluorinated alcohol increased the formation of the alcohol with respect to the ketone.…”
Section: Alkenyl Epoxidessupporting
confidence: 60%
“…After considerable fruitless experimentation with several Lewis acids we eventually explored a palladium-catalyzed isomerization approach pioneered by Noyori48 and modified more recently by Radinov 49. Under the latter conditions, opening of vinyl epoxide 32 in the presence of a fluorinated alcohol proceeded to furnish hemiacetals 33 α and 33 β as an inseparable mixture of diastereomers.…”
Section: Resultsmentioning
confidence: 99%
“…The three A-rings, in the form of the allyldiphenylphosphane oxides 17 ,24-26 18 ,27-29 and 19 30-32 were used in Wittig-Horner reactions with the six CD-ring units 12S-b, 14S-b, 16S-b and their ( R )-counterparts which, after deprotection with TBAF, afforded 18 combinations as final products ranging from 2S-1 to 4R-3 (Scheme 4). The crystal structure of one of them ( 2R-2 ) is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%